TRENDS IN THE DEVELOPMENT OF THE DIGITAL ECONOMY AND THE CORPORATE ENVIRONMENT OF ENTREPRENEURSHIP - KHARCHENKO, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article discusses the trends in the development of the digital economy and the corporate environment of entrepreneurship in the context of interaction in harmonizing the interests of the corporation, employees and family members. Accelerated technological development has revolutionized society and continues to penetrate all spheres of life. The development of social and economic relations depends on the progress of information and digital technologies. The key features of the modern economy are the emergence of the concept of the information society, the development of the digital economy and the rapid transformation of digital changes in all areas of activity. Today, the dynamics of the economic system will be determined by the innovative activity of business entities as the most progressive, adaptive and flexible sector of the economy, the level of commercialization of innovative developments and the increased demand for scientific and technological innovations, such as the digitalization of the entire business process. Digital transformation is a manifestation of qualitative, revolutionary changes that consist not only of individual digital transformations but also of a fundamental change in the structure of the economy, the transfer of value creation centers to the sphere of building digital resources and end-to-end digital processes. As a result of digital transformation, there is a transition to a new technological and economic structure, as well as the development of new sectors of the economy. Ongoing digital transformations have led to a change in the models of development of digital economy competencies based on the following key guidelines: integration; aggregation; cooperation; creation; learning; collaboration, interaction, subject to the alignment of the interests of the corporation, employees, family members in the following chains In view of the ongoing transformation of business models, the digital economy should be understood as building business processes and forming business models based on the capabilities of digital technologies and big data exchange in order to increase business competitiveness by enhancing customer value and achieving key results - reducing costs and increasing productivity.